Decision-making in international organizations: institutional design and performance - Thomas Sommerer; Theresa Squatrito; Jonas Tallberg; Magnus Lundgren (The Review of International Organizations, 2021)
International organizations (IOs) experience significant variation in their decision-making performance, or the extent to which they produce policy output. While some IOs are efficient decision-making machineries, others are plagued by deadlock. How can such variation be explained? Examining this question, the article makes three central contributions. First, we approach performance by looking at IO decision-making in terms of policy output and introduce an original measure of decision-making performance that captures annual growth rates in IO output. Second, we offer a novel theoretical explanation for decision-making performance. This account highlights the role of institutional design, pointing to how majoritarian decision rules, delegation of authority to supranational institutions, and access for transnational actors (TNAs) interact to affect decision-making. Third, we offer the first comparative assessment of the decision-making performance of IOs. While previous literature addresses single IOs, we explore decision-making across a broad spectrum of 30 IOs from 1980 to 2011. Our analysis indicates that IO decision-making performance varies across and within IOs. We find broad support for our theoretical account, showing the combined effect of institutional design features in shaping decision-making performance. Notably, TNA access has a positive effect on decision-making performance when pooling is greater, and delegation has a positive effect when TNA access is higher. We also find that pooling has an independent, positive effect on decision-making performance. All-in-all, these findings suggest that the institutional design of IOs matters for their decision-making performance, primarily in more complex ways than expected in earlier research.
Keywords: 320; International organizations; Institutional design; Decision-making; Global governance; Performance